2008
DOI: 10.1111/j.1601-5215.2008.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of unipolar depression with gene polymorphisms in the serotonergic pathways in Han Chinese

Abstract: The study demonstrates that 5-HTTLPR and 5-HT2CR Cys23Ser polymorphisms might contribute to susceptibility of UPD, and the genotype T/T in 5-HT1DβR T371G polymorphism might be a risk factor for diurnal variation, while T/G might be a protective factor against hopelessness in Han Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A total of 39 studies, comprising k =46 independent samples published between 1996 and 2009, were identified by the search strategy and contributed to the meta-analysis (Collier et al 1996; Kunugi et al 1997; Rees et al 1997; Bellivier et al 1998; Furlong et al 1998; Hoehe et al 1998; Ohara et al 1998; Oliveira et al 1998; Frisch et al 1999; Kim et al 2000, 2007; Shcherbatykh et al 2000; Mellerup et al 2001; Minov et al 2001; Serretti et al 2002; Steffens et al 2002; Caspi et al 2003; Hauser et al 2003; Mendlewicz et al 2004; Hoefgen et al 2005; Taylor et al 2005; Willis-Owen et al 2005; Bozina et al 2006; Cervilla et al 2006; Grunblatt et al 2006; Munafò et al 2006; Surtees et al 2006; Wilhelm et al 2006; Zalsman et al 2006; Chipman et al 2007; Dorado et al 2007; Middeldorp et al 2007; Otte et al 2007; Philibert et al 2007; Shi et al 2008; Zaboli et al 2008; Laucht et al 2009; Wray et al 2009; Zhang et al 2009). Of these, k =33 samples were derived from populations of European ancestry, k =6 from populations of East Asian ancestry, and k =7 from other populations.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 39 studies, comprising k =46 independent samples published between 1996 and 2009, were identified by the search strategy and contributed to the meta-analysis (Collier et al 1996; Kunugi et al 1997; Rees et al 1997; Bellivier et al 1998; Furlong et al 1998; Hoehe et al 1998; Ohara et al 1998; Oliveira et al 1998; Frisch et al 1999; Kim et al 2000, 2007; Shcherbatykh et al 2000; Mellerup et al 2001; Minov et al 2001; Serretti et al 2002; Steffens et al 2002; Caspi et al 2003; Hauser et al 2003; Mendlewicz et al 2004; Hoefgen et al 2005; Taylor et al 2005; Willis-Owen et al 2005; Bozina et al 2006; Cervilla et al 2006; Grunblatt et al 2006; Munafò et al 2006; Surtees et al 2006; Wilhelm et al 2006; Zalsman et al 2006; Chipman et al 2007; Dorado et al 2007; Middeldorp et al 2007; Otte et al 2007; Philibert et al 2007; Shi et al 2008; Zaboli et al 2008; Laucht et al 2009; Wray et al 2009; Zhang et al 2009). Of these, k =33 samples were derived from populations of European ancestry, k =6 from populations of East Asian ancestry, and k =7 from other populations.…”
Section: Resultsmentioning
confidence: 99%
“…Similar male‐specific associations between the S allele and anxiety [Du et al, ] or emotion disorders [Wang et al, ] have been reported in previous studies. The gender difference may account for the inconsistent results [Flory et al, ; Lang et al, ; Ohira et al, ; Shi et al, ;] for the association between 5‐HTTLPR polymorphism and neuroticism‐related traits and disorders reported by others. Note that some studies of female Caucasians found an association between 5‐HTTLPR polymorphism and neuroticism‐related traits [Melke et al, ; Xenia Gonda et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The genotype distribution is quite different in different ethnic populations, with the s/s allele prevalence around 12–24% in Caucasians but around 45–74% in East Asians [20]. In Asian populations, some studies found a significant association between the s allele and affective disorder [21], but more studies found no significant association [22][25] and one study even found that the l allele of 5-HTTLPR was more common in major depression disorder (MDD) group than in healthy controls [26]. A recent meta-analysis study also found that the s/s genotype was significantly associated with an increased risk of MDD among Caucasian population but not among Asians [10].…”
Section: Introductionmentioning
confidence: 99%